Membrane association and release of wild-type and pathological tau from organotypic brain slice cultures - Croft, Cara L (Cell Death Dis, 2017)
The spatiotemporal transmission of pathological tau in the brain is characteristic of Alzheimer's disease. Release of both soluble and abnormal tau species from healthy neurons is increased upon stimulation of neuronal activity. It is not yet understood whether the mechanisms controlling soluble tau release from healthy neurons is the same as those involved in the spread of pathological tau species. To begin to understand these events, we have studied tau distribution and release using organotypic brain slice cultures. The slices were cultured from postnatal wild-type and 3xTg-AD mice for up to 1 month. Tau distribution in subcellular compartments was examined by western blotting, and tau release into culture medium was determined using a sensitive sandwich ELISA. We show here that 3xTg-AD cultures have an accelerated development of pathological tau abnormalities including the redistribution of tau to synaptic and membrane compartments. The 3xTg-AD slice cultures show elevated basal tau release relative to total tau when compared with wild-type cultures. However, tau release from 3xTg-AD slices cannot be further stimulated when neuronal activity is increased with potassium chloride. Moreover, we report that there is an increased pool of dephosphorylated membrane-associated tau in conditions where tau release is increased. These data suggest that there may be differential patterns of tau release when using integrated slice culture models of wild-type and transgenic mouse brain, although it will be important to determine the effect of tau overexpression for these findings. These results further increase our knowledge of the molecular mechanisms underlying tau release and propagation in neurodegenerative tauopathies.